2024
DOI: 10.3390/s24030743
|View full text |Cite
|
Sign up to set email alerts
|

Compact and Fully Integrated LED Quantum Sensor Based on NV Centers in Diamond

Jens Pogorzelski,
Ludwig Horsthemke,
Jonas Homrighausen
et al.

Abstract: Quantum magnetometry based on optically detected magnetic resonance (ODMR) of nitrogen vacancy centers in diamond nano or microcrystals is a promising technology for sensitive, integrated magnetic-field sensors. Currently, this technology is still cost-intensive and mainly found in research. Here we propose one of the smallest fully integrated quantum sensors to date based on nitrogen vacancy (NV) centers in diamond microcrystals. It is an extremely cost-effective device that integrates a pump light source, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…The developed system also offers advantages outside of laboratory environments. By replacing the SLAprinted structure with a compact sensor head, as in Pogorzelski et al [2], or by extending a fiber-coupled system, a variety of interesting applications arise for the commercial sector. With the four orientations of the NV centers, vector magnetometry for static or slowly changing magnetic fields can be realized using ODMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed system also offers advantages outside of laboratory environments. By replacing the SLAprinted structure with a compact sensor head, as in Pogorzelski et al [2], or by extending a fiber-coupled system, a variety of interesting applications arise for the commercial sector. With the four orientations of the NV centers, vector magnetometry for static or slowly changing magnetic fields can be realized using ODMR.…”
Section: Discussionmentioning
confidence: 99%
“…Some integrated sensors have already demonstrated that they could achieve sensitivities of 344 pT/ √ Hz and that the performance can already exceed those of conventional Hall sensors [1]. The focus is often on miniaturizing the sensor head with the diamond, radio frequency (RF) excitation via an antenna, and a photodiode for detection as a compact component [1][2][3][4]. However, these sensors still require laboratory measuring instruments to evaluate the weak photocurrent signal and are, therefore, anything but easy to transport.…”
Section: Introductionmentioning
confidence: 99%